MODERN PEDAGOGICAL TECHNOLOGIES FOR DEVELOPING SPEAKING SKILLS IN FOREIGN LANGUAGE EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the principles of systematically developing speech skills in foreign language teaching, as well as ways to foster free thinking in communication and the ability to express one’s ideas orally and in written form according to various communicative situations. In learning foreign languages, listening comprehension, reading comprehension, writing, and speaking skills are of great importance. Speaking and writing skills, as forms of productive language activity, are developed gradually through a step-by-step process. The effective use of modern educational technologies in developing speech competence expands opportunities for fluent communication in foreign languages.